2018
DOI: 10.12688/f1000research.14136.1
|View full text |Cite
|
Sign up to set email alerts
|

Re-highlighting the action of PPARγ in treating metabolic diseases

Abstract: Peroxisome proliferator-activated receptor γ (PPARγ) is a member of the nuclear receptor family and plays an important role in adipocyte differentiation, glucose homeostasis, and insulin sensitivity. Thiazolidinediones (TZDs), synthetic ligands of PPARγ, have been used for the treatment of diabetes mellitus for two decades. TZDs were expected to be amazing drugs not only for type 2 diabetes but also for metabolic syndrome and atherosclerotic vascular disease because they can reduce both insulin resistance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 76 publications
1
13
1
Order By: Relevance
“…Peroxisome proliferator-activated receptor-c (PPARc) is a critical transcription factor in regulating adipogenesis in adipose tissues 4 . PPARc plays important roles in the regulation of lipids, and glucose metabolism and insulin sensitivity [5][6][7] , and thus is associated with the control of obesity and related diseases 7 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Peroxisome proliferator-activated receptor-c (PPARc) is a critical transcription factor in regulating adipogenesis in adipose tissues 4 . PPARc plays important roles in the regulation of lipids, and glucose metabolism and insulin sensitivity [5][6][7] , and thus is associated with the control of obesity and related diseases 7 .…”
Section: Introductionmentioning
confidence: 99%
“…PPARc1 is widely expressed, whereas PPARc2 is predominately expressed in adipose tissue 5,6 . PPARc is the molecular target of thiazolidinediones (TZDs), which have been used in treating diabetes mellitus for two decades 4 . TZDs have many beneficial effects by improving insulin sensitivity 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-translational modifications of PPARγ orchestrate various functions of the protein [18,25,26]. In obesity, phosphorylation of PPARγ on the Ser273 residue by CDK5 leads to dysregulation of a specific gene set [28].…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional activity of PPARγ is activated by its ligands, which include thiazolidinediones (TZDs) [24]. In addition to its ligands, recent studies demonstrated that post-translational modifications (PTMs) of PPARγ, including phosphorylation, small ubiquitin-like modifier (SUMO)-ylation, acetylation, and ubiquitination, are major regulatory mechanisms of PPARγ activation and PPARγ-mediated gene transcription [18,25,26]. Of these, phosphorylation is thought to be a crucial regulator of the transcriptional regulatory activity of PPARγ.…”
Section: Introductionmentioning
confidence: 99%